2014
DOI: 10.1371/journal.pone.0092012
|View full text |Cite
|
Sign up to set email alerts
|

Vaccination against Endogenous Retrotransposable Element Consensus Sequences Does Not Protect Rhesus Macaques from SIVsmE660 Infection and Replication

Abstract: The enormous sequence diversity of HIV remains a major roadblock to the development of a prophylactic vaccine and new approaches to induce protective immunity are needed. Endogenous retrotransposable elements (ERE) such as endogenous retrovirus K (ERV)-K and long interspersed nuclear element-1 (LINE-1) are activated during HIV-1-infection and could represent stable, surrogate targets to eliminate HIV-1-infected cells. Here, we explored the hypothesis that vaccination against ERE would protect macaques from acq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 66 publications
1
5
0
Order By: Relevance
“…Thus, the LL15- and PA8-specific T cell responses in r02120 likely represent genuine targeting of SERV-K1 Env and not cross-reactive SIV-specific T cell responses. This is in line with a previous report indicating lack of SIV-induced up-regulation of SERV activity in the cells of rhesus macaques [ 21 ]. Thus, viral infection status alone does not predict SERV-K1-specific T cell immunity.…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…Thus, the LL15- and PA8-specific T cell responses in r02120 likely represent genuine targeting of SERV-K1 Env and not cross-reactive SIV-specific T cell responses. This is in line with a previous report indicating lack of SIV-induced up-regulation of SERV activity in the cells of rhesus macaques [ 21 ]. Thus, viral infection status alone does not predict SERV-K1-specific T cell immunity.…”
Section: Resultssupporting
confidence: 93%
“…ELISPOT screening was carried out as previous described [ 26 ] using 15-mer peptides (with 11 amino acid overlap) spanning the entire SERV-K1 Env open reading frame or the entire SIVmac239 proteome. Intracellular cytokine staining assays were carried out as previously described [ 21 , 26 ]. Positive responses shown were confirmed using peptides synthesized by three independent sources.…”
Section: Methodsmentioning
confidence: 99%
“…In contrast, the small env -containing family, HK2, may have continued to replicate exclusively in humans. The apparent extinction of the sister lineage of HK2 in the macaque is significant as this lineage is being investigated as a model for testing a possible ERV-based immunotherapy for HIV in humans [ 20 , 30 , 31 ]. The extinction explains why other studies have reported finding only a few full-length ORFs in this family [ 20 , 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…While SIVmac239 and SIVmac251 have a degree of resistance to antibody-mediated neutralization comparable to or exceeding typical circulating HIV-1 strains [52–54**], the SIVsmE660 isolate is composed of viral clones most of which are relatively more neutralization sensitive [48], making it a more tractable target for antibody-based prevention studies. However, unlike the SIVmac viruses, SIVsmE660 and E543 are highly susceptible to restriction by specific rhesus macaque TRIM5α alleles [5558], which can impact virus acquisition after mucosal challenge [57,58], confounding the interpretation of vaccine efficacy [59,60]. Thus, when using SIVsmE660 and related challenge viruses, it is critical to genotype study animals for their TRIM5α alleles and either exclude those with restrictive TRIM5α alleles or account for the distribution of restrictive and permissive alleles among the study arms.…”
Section: Challenge Virusesmentioning
confidence: 99%